ANALYSIS OF REMAINING SERVICE LIFE OF PAVEMENT ON THE SUMENGKO – BANDUNGREJO ROAD SECTION BOJONEGORO REGENCY STA 0+000 TO 2+770 - Adilat Ahmad Firdausyi; Hanie Teki Tjendani; Iswandaru Widyatmoko (Adisam Publisher, 2026)
Bojonegoro Regency is located in East Java Province, west of the provincial capital. The regency covers an area of ​​230,706 hectares and borders seven other regencies. [1]. Bojonegoro as a contributor of 25 percent of national production has made Bojonegoro designated as the location for implementing the National Strategic Program (PSN) for the construction of a bioethanol factory [2]. The planned location is in Gayam District, Bojonegoro Regency. The location has been visited by two investors [2]. The road section that is the main access point for the planned bioethanol factory location is the Sumengko – Bandungrejo road section STA 0+000 - 2+770. Due to the importance of this road section to support the National Strategic Project (PSN), it is necessary to estimate the remaining planned life of the road and estimate the cost of road rehabilitation for current conditions. The remaining planned life is calculated using the AASHTO 1993 method dan Manual Desain Perkerasan Jalan (MDP) 2024 with LHR data in 2023 which will then be calculated to be actual CESAL in 2027 and 2033. Furthermore, the analysis of road rehabilitation costs is calculated according to the guidelines SE Direktur Jenderal Bina Konstruksi 30/SE/Dk/2025 with unit price data and technical data. The remaining services life of the road based on the actual CESAL in 2027 is 67.54% and based on the actual CESAL in 2033 it is 46.43%. The road rehabilitation costs required are Rp. 1,828,617,800.00 to overlay asphalt on spot 2 (STA 0+750 to 1+900) and repair of road shoulders with gabions amounting to Rp. 141,563,400.00 on spot 3 (STA 2+000 to 2+020).